2018
DOI: 10.1116/1.5022068
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial titanium nitride on sapphire: Effects of substrate temperature on microstructure and optical properties

Abstract: Titanium nitride (TiN) is a mechanically robust, high-temperature stable, metallic material receiving considerable attention for resilient plasmonics. In this work, the authors fabricated six heteroepitaxial TiN films on sapphire using controllably unbalanced reactive magnetron sputtering. They examined the effect of substrate growth temperature on the plasmonic and crystalline quality of the film. Optical properties of all films were obtained from spectroscopic ellipsometry; plasmonic quality factors were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…Previous works have demonstrated that crystalline properties and surface morphologies of Ag films and nanostructures play an important role in plasmonic applications. Especially, uniform and controllable plasmonic hotspots can be realized by high-fidelity top-down nanofabrication on ultrasmooth, single-crystalline Ag colloidal crystals. , In addition to epitaxial Ag films, , other plasmonic materials, such as Au, copper (Cu), titanium nitride (TiN), and Al films grown on miscellaneous substrates have been successfully developed for plasmonic applications , , and 2D material growth templates. , The epitaxial growth approach offers many distinctive advantages for plasmonic applications, such as formation of large-area (wafer scale), low-loss (single crystalline), and ultrathin ( e . g ., tunable through gating and quantum optical effects) metal layers for top-down plasmonic device fabrication.…”
Section: Resultsmentioning
confidence: 99%
“…Previous works have demonstrated that crystalline properties and surface morphologies of Ag films and nanostructures play an important role in plasmonic applications. Especially, uniform and controllable plasmonic hotspots can be realized by high-fidelity top-down nanofabrication on ultrasmooth, single-crystalline Ag colloidal crystals. , In addition to epitaxial Ag films, , other plasmonic materials, such as Au, copper (Cu), titanium nitride (TiN), and Al films grown on miscellaneous substrates have been successfully developed for plasmonic applications , , and 2D material growth templates. , The epitaxial growth approach offers many distinctive advantages for plasmonic applications, such as formation of large-area (wafer scale), low-loss (single crystalline), and ultrathin ( e . g ., tunable through gating and quantum optical effects) metal layers for top-down plasmonic device fabrication.…”
Section: Resultsmentioning
confidence: 99%
“…However, the majority of the demonstrations of TiN's device potential in plasmonics have been on sapphire and bulk MgO substrates featured by their small lattice mismatch with TiN, enabling the best‐performing plasmonic films. [ 24,28–33 ] Even then, high deposition temperatures (not congruent with CMOS processes) were usually used to ensure the high structural quality of the TiN films. For example, using reactive sputtering and at a substrate temperature of 650 °C, a peak plasmonic figure of merit (FOM = − ε ′/ ε ″) of ≈4.5 has been demonstrated for TiN films on a bulk MgO substrate.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] In the area of plasmonics, TiN-based waveguides, [19] gyroidal metamaterials, [20] nanohole metasurfaces, [21] nanoantennas, [22][23][24] and use of TiN nanoparticles for solar energy conversion [25,26] and biomedicine [27] have been reported.However, the majority of the demonstrations of TiN's device potential in plasmonics have been on sapphire and bulk MgO substrates featured by their small lattice mismatch with TiN, enabling the best-performing plasmonic films. [24,[28][29][30][31][32][33] Even then, high deposition temperatures (not congruent with CMOS processes) were usually used to ensure the high structural quality of the TiN films. For example, using reactive sputtering and at a substrate temperature of 650 C, a peak plasmonic figure of merit (FOM ¼ Àε 0 /ε 00 ) of %4.5 has been demonstrated for TiN films on a bulk MgO substrate.…”
mentioning
confidence: 99%
“…The rocking curve revealed a fullwidth-half-maximum (FWHM) of 0.04 • . To the best of our knowledge, this is among the best reported sputtered TiN films and even some of the TiN films grown via molecular-beam epitaxy [23,27,31]. Low temperature deposition of high-quality epitaxial TiN thin films was reported but has been done with a heavily customized sputtering system to modify the magnetic flux lines [31][32][33].…”
Section: A Structural Characterizationmentioning
confidence: 99%
“…To the best of our knowledge, this is among the best reported sputtered TiN films and even some of the TiN films grown via molecular-beam epitaxy [23,27,31]. Low temperature deposition of high-quality epitaxial TiN thin films was reported but has been done with a heavily customized sputtering system to modify the magnetic flux lines [31][32][33]. As such, using a low thermal budget deposition process with a readily used commercial deposition system present opportunities for material investigation, process optimization, and device integration in future works.…”
Section: A Structural Characterizationmentioning
confidence: 99%